Federalism and the challenges of ethnic conflict regulation in deeply divided society: the case of Iraq - Hama, Yaseen (2018)
Bad governance of ethnic diversity exacerbates ethno-sectarian conflicts, and ethnic conflict management is a sensitive and fundamentally needed component of the contemporary world. This study assesses political models for managing ethno-sectarian diversity, focused on the deeply divided society of Iraq in relation to its ethnic conflict and political system, with federalism and partition being potential solutions explored in relation to stakeholders’ views, studied qualitatively using focus groups and interviews with procedure and analysis derived from grounded theory. Due to failed integration, Iraqi society since 2003 has undergone de facto territorial division in response to ethno-sectarian violence, creating a map between conflicting groups and identity politics. This thesis criticizes integrationist perspectives supporting a central unitary Iraq, and those proposing hard partition; federal-based soft partition, giving each cultural group control and autonomy in their territory, may achieve stability, whereas secession is impossible. This balances Shia desire for centralism and Kurdish demands for more autonomy or secession. In addition, it is not necessary to impose a single national identity in federal model; dual identity should be accepted to satisfy groups’ identity aspirations. The current impasse is due to authoritarian centralism imposing monolithic identity; Iraq should be a democratic multicultural state, avoiding sectarian policy and implementing civic characteristics to enhance Iraqi identity. This study contributes to existing research, analysing how inappropriate policies of ethnic diversity may escalate into ethnic conflicts. This thesis adds to the field of studies interested in ethnic conflict regulation, particularly Iraqi ethno-sectarian conflict, and provides suggestions for regulating it.